2016
DOI: 10.1177/2158244016638393
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of Parenting Styles on Children’s Social Skills

Abstract: The aim of this study was to investigate the relationship between parenting styles and children's social skills, establishing significant correlations between those two constructs. A total of 202 children, 7 to 10 years old, male and female, attending second to fourth year of government schools in São Paulo, Brazil, were participants of this research. They collectively completed Children's Social Skills Test (THAS-C) and Parental Styles Inventory (IEP). Results suggest that positive parental styles are predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…Additionally, the research by Bartholomeu et al (2016) found that social skills as civility, apologizing, helping others, altruism, gratefulness, assertiveness were associated with positive and negative parental styles. This is the reason why studies should investigate associations between specific maternal and child's behaviours, aiming at better comprehending these kinds of data and findings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the research by Bartholomeu et al (2016) found that social skills as civility, apologizing, helping others, altruism, gratefulness, assertiveness were associated with positive and negative parental styles. This is the reason why studies should investigate associations between specific maternal and child's behaviours, aiming at better comprehending these kinds of data and findings.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial research on authoritative parenting and the importance of both developmentally appropriate demandingness and sufficient warmth and support (Bartholomeu, Montiel, Fiamenghi, & Machado, 2016;Baumrind, 1971;Baumrind, 1991;Gunnoe, Hetherington, & Reiss, 1999;Pinquart, 2016;Smetana, 2017;Steinberg, Lamborn, Darling, Mounts, & Dornbusch, 1994). Some prominent researchers have even gone so far as to say that there is enough evidence to support the use of authoritative parenting that research efforts should be directed to other areas (Steinberg, 2001).…”
Section: Parentingmentioning
confidence: 99%
“…There is a high degree of consensus among researchers about effective and ineffective approaches to parental discipline. Studies show that spanking, name-calling, offending, threatening, and other forms of harsh discipline are unconstructive, and tend to generate undesirable future behavior (Bartholomeu et al, 2016;Gershoff & Grogan-Kaylor, 2016;Gershoff, 2002;Gershoff et al, 2010;Kremer, Smith, & Lawrence, 2010;Locke & Prinz, 2002;McKee et al, 2007;Straus & Donnelly, 1993). Although physical punishment may enforce immediate compliance, in the long term it undermines children's trust in parents and their willingness to obey (Gershoff, 2002).…”
Section: Parental Disciplinary Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of such a relationship with nature shifts to everyday life and makes a lasting diversion of a way of thinking. It has been reported that outdoor education can change the way of thinking and even good for maintaining health and focus on keeping cultural dynamics that support the appreciation of nature, diverse senses, and assertiveness (Bartholomeu, Montiel, Fiamenghi, & Machado, 2016).…”
Section: Introductionmentioning
confidence: 99%